ANALISIS KENAIKAN BERAT BADAN BALITA SELAMA PANDEMI COVID-19 DI PUSKESMAS SANOBA KABUPATEN NABIRE TAHUN 2022 - Christina Tien Popang; Fanny Seleki; Maya Siti Maemunah (NHM PRESS, 2022)
Toddlers are children aged 0-59 months, this period is characterized by a process of growth and development that is very rapid and is accompanied by changes that require nutrients in greater quantities with high quality. However, toddlers are a group that is vulnerable to nutrition and easily suffers from nutritional disorders due to a lack of the food they need. The social and economic crisis caused by the coronavirus pandemic has the potential to cause nearly seven million children to be stunted due to malnutrition, says the United Nations. The purpose of this study is that researchers want to know